2013
DOI: 10.4274/jcrpe.994
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Complications in Adolescents with Type 1 Diabetes Mellitus

Abstract: Objective: Screening of complications is an important part of diabetes care. The aim of this study was to investigate diabetic complications and related risk factors in adolescents with type 1 diabetes mellitus (T1DM).Methods: This cross-sectional study was conducted on type 1 diabetics who were over 11 years of age or had a diabetes duration of 2 years and included 155 adolescents with T1DM (67 male, 88 female). The mean age of the patients was 14.4±2.1 years. Mean diabetes duration was 6.3±2.9 years. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
6
25
3
Order By: Relevance
“…Some research in children and adolescents with DM done in the USA and Australia found rates of microvascular complication that were similar or even higher than those found here, but these studies used more sensitive diagnostic tests [16,24]. Most research from Western countries showed significantly lower microvascular complication rates, such as one study done in in Ankara, Turkey that found a 16.1% rate of microalbuminuria, 0.6% rate of neuropathy, and no cases of retinopathy [25].…”
Section: Discussionsupporting
confidence: 63%
“…Some research in children and adolescents with DM done in the USA and Australia found rates of microvascular complication that were similar or even higher than those found here, but these studies used more sensitive diagnostic tests [16,24]. Most research from Western countries showed significantly lower microvascular complication rates, such as one study done in in Ankara, Turkey that found a 16.1% rate of microalbuminuria, 0.6% rate of neuropathy, and no cases of retinopathy [25].…”
Section: Discussionsupporting
confidence: 63%
“…This can infl uence negatively the adaptation of the adolescent in relation to diabetes, cooperating or not with the disease control [9][10][11][12][13][14][15] . The family then worry in an exaggerated manner, and to convey feelings of anxiety and fear in relation to immediate and late complications of the disease, not only when the adolescent doesn't follow treatment properly, causing the same feel and think the same way 22 .…”
Section: "The Complications and Some Injury In Some Organ Scare Me" (mentioning
confidence: 99%
“…Healthy habits for the individual with DM1 should be used daily by the capillary blood glucose control, insulin therapy and regular physical activity, which are considered of utmost importance to prevent and delay chronic and acute complications and hospitalizations [12][13] . That's why Marques, Fornés, Stringhini 14 also stress that proper treatment for the control of acute episodes of Hyperglycemia or hypoglycemia can prevent the development of common diseases in those circumstances as Neuropathies, kidney diseases and cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Careful glycemic control is challenging and it is well known that hyperglycemia leads to several complications including nephropathy despite existing therapeutic measures [3,4]. Approximately 25 % of patients with type 1 and type 2 diabetes develop renal injury [5,6].…”
Section: Introductionmentioning
confidence: 99%